Risk and protective factors related to having a child with congenital heart diseases (CHD): a case-control study in Iran - Amini-Rarani, Mostafa; Karimi, Salah Eddin; SoleimanvandiAzar, Neda; Nosratabadi, Mehdi (Frontiers in Pediatrics, 2023)
Background The heart is the first fully developed organ in early pregnancy, especially in the first trimester of pregnancy, so any factor that contributes to heart failure is life-threatening. Thus, it is important to identify the risk and preventive factors related to this disease and to provide a scientific basis for the control, prevention, management and treatment of Child with Congenital Heart Diseases (CHD). Objectives As the etiology of CHD is multifactorial, to identify the risk and preventive factors, this study aimed to investigate the factors related to CHD in Tehran, Iran. Methods The present case-control study was performed on 600 people including 200 mothers of children with CHD. Simple random sampling was performed in 2020. The control group was matched with the case group, and the data were analyzed by SPSS software at a significance level of 0.5. Results The results showed that low socioeconomic status, low education, history of abortion, smoking, alcohol consumption are risk factors, and consumption of folic acid, and prenatal care are the protective factors against CHD. Conclusion According to the findings, our emphasis should be on preventive strategies, education of mothers and public health experts on the need for folic acid and pregnancy care, and cessation or reduction of alcohol and tobacco use, especially in families with low socioeconomic status and low level of education.